IMPLEMENTASI PATIENT CASE MANAGER DALAM PENANGGULANGAN TUBERKULOSIS DI RUMAH SAKIT UMUM MUHAMMADIYAH METRO - Pertiwi, Windi; Mayasari, Fitri Yuli; Putra, Yogi Catur; Angguniar, Eva Nirmala; Safira, Retno Sofy (LPPM Universitas Awal Bros, 2026)
Tuberculosis remains a major global health problem with challenges in treatment adherence, loss to follow-up, and treatment completion. Patient Case Manager (PCM) is considered an important strategy to improve tuberculosis management through systematic patient assistance and monitoring. This study aimed to analyze differences in tuberculosis treatment outcomes before and after the implementation of Patient Case Manager at Muhammadiyah Metro General Hospital. This study used a quantitative retrospective comparative design with a before–after approach. The study population consisted of all tuberculosis patients recorded in the hospital tuberculosis information system from 2021–2024. Sampling was conducted using total sampling technique. Data analyzed included number of diagnosed patients, patients undergoing treatment, and treatment success rates before and after PCM implementation. Statistical analysis used Chi-square test with significance level p<0.05. The results showed that tuberculosis case detection increased from 333 patients before PCM implementation to 818 patients after implementation. The number of patients undergoing treatment also increased from 199 to 350 patients. Treatment success rate increased from 96.0% before PCM implementation to 97.1% after implementation. Statistical analysis showed significant differences in treatment indicators before and after PCM implementation (p<0.05). In conclusion, the implementation of Patient Case Manager contributed to improved tuberculosis case detection, patient treatment participation, and treatment success rates. Strengthening the role of Patient Case Manager is recommended to optimize tuberculosis control programs in hospitals.